PENERAPAN MEKO NUMHETOG BERBANTUAN MEDIANI UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR MAPEL SINANDUNG DI SMK NEGERI 2 PURWOKERTO - Karsukmia Nandja (Sekolah Tinggi Pariwisata Mataram, 2023)
The researched aims to apply the Numhetog (Number Head Together) Cooperative Learning Model assisted by Mediani (Animated Media) to increased the activities and learning outcomes of students in the Sinandung subject (Construction of Buildings) at SMK Negeri 2 Purwokerto. Researchers used observation techniques from data facts that were used as the basis for classroom action research. The researcher identified the problem so that alternative learning improvements were found. The numhetog learning model (NHT), with animated media, makes learning more innovative, active, creative and fun. Class action research with initial conditions (pre-cycle), actions (Cycles 1 and 2), and final conditions. The results of the research on student learning activities increased 12.12% from pre-cycle activities to cycle I, and increased 6.79% from cycle I to cycle II activities. An increase in the number of students achieving the minimum completeness criteria (KKM) of 60.61% in cycle I. It increased to 78.80% in cycle II and the final cycle reached 89.66% of these students indicating that there was achievement of mixed classical mastery criteria ≥ 85%